Relationship Between Intensity Of Social Media Use And Narcissistic Behavior In Uinsu Tunungan Students (HEALTH CARE: JURNAL KESEHATAN, 2025)
Social media is an internet medium that allows individuals to readily interact, share, and display their presence. The purpose of this study is to ascertain how UINSU Tuntungan students' propensity for narcissism and their level of social media use relate to one another. Up to 105 respondents from four faculties were chosen using the stratified random sample technique in a quantitative cross-sectional design. According to the findings, the majority of respondents reported a moderate inclination toward narcissism (83.8%) and a high one (16.2%). Forty percent of those surveyed fall into the high category for social media use intensity. The degree of social media use and the propensity for narcissism were significantly correlated (p=0.005). These results suggest that the propensity for narcissistic behavior increases with the degree of social media use. This study emphasizes the value of character development and digital literacy in addressing the effects of social media on students' self-identity and mental health